Petrogenesis of the late Archean Singertât Alkaline Igneous Complex, North Atlantic Craton, South-East Greenland - Naidoo, Arantxa (My University, 2019)
The Singertât Complex forms part of the Skjoldungen Alkaline Igneous Province (SAIP, 2760-2690 Ma) located in SE Greenland. It was emplaced into the southern part of the SAIP in a sequence of small, sheet-like intrusions during the Late Archean and was thought until recently to be post-tectonic with previous work suggesting an age of 2680-2660 Ma. The complex consists of a variety of silica undersaturated (nepheline-bearing) alkaline rocks, which occur as modally layered, horizontal sheets cut by minor late-stage nepheline syenite pegmatites and carbonatites. This project aims to understand the petrogenesis of the Singertât Complex, including investigating magmatic processes and crystal cargo dynamics from mantle source to final emplacement in the upper crust. Crucial questions include whether the complex is constructed from single or multiple magma batches, whether those batches were emplaced as crystal-poor liquids or as crystal mushes and what type/s of crystallization processes operated? Detailed petrographic analysis indicates that the Singertât Complex is composed primarily of nepheline-bearing lithologies such as urtite (>70% nepheline), ijolite (70-30% nepheline) and melteigite (<30% nepheline). These alkaline silicate rock types are either equigranular or porphyritic and the main mineral phases include nepheline, orthoclase, microcline, anti-perthite, aegerine-augite, biotite, minor primary carbonate and in some samples sodalite, with accessory magnetite, apatite and zircon. Poikilitic growth relationships suggest that mafic minerals crystallized first followed by nepheline, which appears to have crystallized from the remaining interstitial liquid. Anti-perthite commonly exhibits anastomosing exsolution textures, indicating supersolvus crystallization temperatures above 600 ºC, followed by slow cooling. Both gradational transitions and sharp contacts between rock types are observed. Where sharp boundaries occur, crystal truncation suggests that the pre-existing unit has been chemically or thermally eroded, perhaps as a result of sheet emplacement. Petrographic and geochemical evidence obtained has found that the syenitic gneiss which forms part of the Singertât Complex is actually a nepheline syenite as nepheline crystal were identified during petrographic investigation and confirmed during EPMA analysis. Major element results obtained from EPMA analysis also demonstrate that the nepheline populations found in the syenitic gneisses are similar to the population found in the nepheline-bearing alkaline rocks. This evidence could mean that if the syenitic gneisses have not undergone fenitization then the syenitic gneisses are not host rocks as previously thought but are actually part of the Singertât Complex itself. Major element compositions of the nepheline-bearing alkaline rocks show that while nepheline crystal populations in gradationally layered samples are similar (i.e. from the same magma batch), nepheline populations in samples with sharp contacts are different (i.e. from several discrete magma batches). Petrographic studies and EPMA indicated that the aegerine-augite crystals of the nepheline-bearing rocks were compositionally zoned and many of the aegerine-augite crystals in some samples depict a large crystal size variation with some crystals being as large as 1 cm and others < 1mm within the same rock. This compositional zonation and large variation in crystal size may provide evidence that these aegerine-augite crystals were entrained in a magma which replenished the Singertât magma chamber promoting crystallization as a crystal-rich slurry. Further evidence to support this can be observed in some of the nepheline-bearing alkaline sample, where we observe flow textures with smaller crystals aegerine-augite and nepheline that are aligned around larger crystals. Flow textures are formed from eddie currents, where already crystallized, larger, primocrysts disrupt interstitial liquid flow, causing alignment of the smaller crystals during nucleation. Therefore, it would appear that the Singertât Complex formed as a result of multiple replenishments of crystal-rich magma. Major element analysis also shows that the Singertât is barely peralkaline and is in fact more metaluminous due the results obtained from the alkalinity index. The majority of the samples appear to fall into the category of miaskitic, as they fall within the peraluminous and metaluminous fields on the peralkalinity index and also due to indicator minerals such as zircon present in many of the rock types. New 206Pb/238U zircon age determinations show that the nepheline-bearing pegmatites range from 2785 ± 10 Ma to 2753.4 ± 5.8 Ma, one dated carbonatite returns an age of 2750 ± 11 Ma, a representative ijolite sample is dated at 2771 ± 32 Ma and a representative melteigite sample produces an age of 2774 ± 12 Ma. Not only does this prove that the Singertât Complex is older than previously thought but places the formation of the Singertât Complex outside the Singertât Stage and at the beginning of the Skjoldungen orogeny. These ages also demonstrate that the Singertât Complex may be the oldest alkaline complex in the world. The evidence presented above suggests that the small alkaline Singertât Complex formed during Late Archean orogenesis from multiple batches of crystal-rich magma with subsequent in-situ crystallization as the primary processes involved in layer formation.
A research report submitted at the Faculty of Science, University of the Witwatersrand, Johannesburg for the Degree of Master of Science (Geology), 2019